Abschlussarbeiten an Nordrhein-Westfälischen Designschulen 1989. (Hagen : Karl Ernst Osthaus-Museum, 1989)
Gläntzer, Christina ; Guzinski, Beate ; Hahn, Kerstin Helena ; Husemöller, Beate ; Kuntze, Dagmar ; Stockhaus, Ulrike ; Bouxhein, Reiner ; Wichmann, Petra ; Beyle, Jürgen ; Enker, Norbert ; Erler, Detlef ; etc.
Abschlussarbeiten an Nordrhein-Westfälischen Designschulen 1989, Karl Ernst Osthaus-Museum, Hagen, 17.11. - 03.12.1989
boek